The interaction between bureaucrats and military in the second period of Fatimid caliphate in Egypt (1100-1180) - m Heydari (پژوهش های تاریخی, 2013)
Fatimid caliphate (900-1180) which was established in the North of Africa as a rival government for Abbasid caliphate(750-1258) enjoyed particular political, administrative, and military features. The religious leaders of Ismailia in the Hidden Call period along with Da’ah network and their scattered but organized disciples could manage to found Fatimid caliphate and formally take up the political and military power in 900 AD. Likewise, there was a great development from informal to formal condition in the Ismailia Imam’s status and position and his circles, during which the power was organized, and Ismailia society elements were reconceptualized in terms of the current conventional administrative, political and military organs. The bureaucratic and military structure was under the influence of political and social Ismailia pedagogy and the demands of Shiite caliphate lasting for about two centuries. The most significant reasons for their fall were the bureaucratic and military structure, the state of interaction between bureaucrats and military, as well as the influential factors. The present study aims at describing and analyzing the bureaucratic and military structure and the reasons for the convergence and divergence in the above-mentioned interactions in order to answer the questions concerning the way bureaucrats and military interacted and the factors which influenced the interaction in the second period of Fatimid caliphate.